Serious Game con RV basado en musicoterapia aplicado al mejoramiento del aprendizaje de niños con TDAH. - Salazar Chiquito, Alejandro Jossua (2023)
Attention Deficit Hyperactivity Disorder (ADHD) is a disorder with significant impact on child neurodevelopment. Various research studies have provided evidence of the efficacy of two therapeutic approaches that have proven to be effective in the treatment of ADHD, specifically virtual reality games and music therapy. However, these studies have addressed these treatments independently, without directly comparing them. Therefore, the purpose of this study is the design and implementation of a serious virtual reality game based on music therapy, emphasizing the attention difficulties present in the learning of children aged 8 to 12 with ADHD. The results obtained from this study show data evaluated by a specialist that demonstrate the efficacy in ADHD patients when serious games are applied in combination with music therapy. These patients show a fluid and uninterrupted involvement in the activities, on the contrary, their involvement is altered when these interventions lack the incorporation of music therapy.